Obstacles to the establishment of school sports activities (extracurricular) from the theoreticians of secondary school educators in Souq Ahras, Algeria - Mohammed yahya, Mahdi (sports creativity, 2025)
The research aims to identify the obstacles that prevent the establishment of school sports activities (extracurricular) from the perspective of high school educators, to identify the rate of practice of extracurricular sports activities in secondary schools, so used the descriptive curriculum, including the sample of research (40) educators in the state of Souq Ahras, research tools the researcher used a questionnaire form to reach the objectives of the research, the most important findings of the researcher - There are obstacles to the establishment of school sports activities (extracurricular) from the sight of sports educators in secondary schools in The Market Of Ahras, Algeria. - There is a low percentage of school sports activities (extracurricular activities) in some secondary schools in The Market Of Ahras in Algeria.